ُETUDE NUMERIQUE DE LA CONVECTION MIXTE LAMINAIRE DANS DES CAVITES VENTILEES (Sciences & Technologie. B, Sciences de l'ingénieur, 2005)
In this work, we present a numeric study of the phenomenon of laminar mixed convection in a ventilated square cavity, of which one of partitions is submitted to a constant temperature, while the other partitions are considered like adiabatic. Equations governing this phenomenon were discrétised by the method of differences finished and a code of calculation has been developed to determine all the structure of the out-flow. Results are presented under shape of fields streamlined and thermal for different values of numbers of Richardson. These show the apparition of recirculation contrarotatives zones in the superiorpart of the cavity when the forced convection predominates.